2015
DOI: 10.1155/2015/970542
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Evaluation of Polycaprolactone/Gelatin‐Based Electrospun Nanofibers with Antibacterial Properties

Abstract: Nanofibrous scaffolds were fabricated through blending of a synthetic polymer, polycaprolactone (PCL), and a natural polymer, gelatin (GE), using an electrospinning technique. Processing and solution parameters were optimized to determine the suitable properties of PCL/GE-based nanofibers. Several characterizations were conducted to determine surface morphology by scanning electron microscopy (SEM), wettability using water contact angle measurement, and chemical bonding analysis using attenuated total reflecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 20 publications
5
43
0
Order By: Relevance
“…To make the TCH/PCL and TCH/nHA/PCL solution, TCH had to be predissolved in methanol before adding to the solution. 0.2 g TCH was dissolved in 10 mL methanol to load 2% (w/ v) TCH into the nanofibers (Chong et al 2015). After all the TCH was completely dissolved into methanol, 1 mL of TCH solution was taken out and added to the polymer solution.…”
Section: Methodsmentioning
confidence: 99%
“…To make the TCH/PCL and TCH/nHA/PCL solution, TCH had to be predissolved in methanol before adding to the solution. 0.2 g TCH was dissolved in 10 mL methanol to load 2% (w/ v) TCH into the nanofibers (Chong et al 2015). After all the TCH was completely dissolved into methanol, 1 mL of TCH solution was taken out and added to the polymer solution.…”
Section: Methodsmentioning
confidence: 99%
“…According to the conducted studies, the use of nHA particles is expected to have great influence on the development of microstructures and biological and mechanical behavior of composite systems for bone tissue engineering applications. Various researchers have demonstrated that a composite of apatite and collagen scaffolds are a good choice for bone tissue engineering applications . Gelatin, the hydrolyzed form of collagen, is a good candidate for bone tissue engineering due to its similarity to collagen that is the main composition of ECM, also gelatin increase the rate of degradation and cellular adhesion .…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin, the hydrolyzed form of collagen, is a good candidate for bone tissue engineering due to its similarity to collagen that is the main composition of ECM, also gelatin increase the rate of degradation and cellular adhesion . For example, in constructing gelatin/apatite composite in the study by Chong et al , the results indicated apatite crystals germination in line with gelatin fibers. On the other hand, among various polymer composites, PCL/Gel compound has received the most attention.…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that the amino and carboxyl groups in gelatin, which are prone to ionization, result in favorable properties including the creation of more homogeneous fibers in electrospun scaffolds in comparison with pure PCL fibers. On the other hand, excessive use of gelatin can result in the instability of electrospinning process caused by too high concentration of electrical charges . Therefore, the optimal amount of gelatin is expected to be considered in hybrid systems so that stable electrospinning processes could be provided.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, excessive use of gelatin can result in the instability of electrospinning process caused by too high concentration of electrical charges. 11 Therefore, the optimal amount of gelatin is expected to be considered in hybrid systems so that stable electrospinning processes could be provided. Currently, several investigations have concentrated on PCL-based nanocomposite with polymers and ceramics for bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%